(3GdUGOM hGdHGZes - (3eMeO Hf eMeO Hf UGdM GdYHGSj, fXGe GdOjf CHh jYdj, GHf GdgHGQjI , J (B509 (3g` s
(3ChdgG (B:s
(3abGd GdhMT(B: (3GdLOGod hGdfXQ djSG HebOGQ GdLoShe hGdbHhQ dcfg HGdYde hGdHjGf hMOoI GdaDGpO hGddSGf s
(3BNQgG (B:s
(3hdh oJQcoJ LjoK SYjkG heG hMjJ Ef GdaNGQ hGdYdG EQKc ef Ohf GdedG Je GdcJGH fSNkG HMeO Gddg s
(3GfXQ GdLRA GdChd JMJ Qbe (B582 (3COHs
(3efXheI aj Cdaj HjJ Ydi GSdhH cdjdI hOefIs
(3fXegG HcQeGfs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3JHUQI GdYfhGf (B:s
Keywords: (3GdCOHs